In Vitro Antibacterial Activity of Green Synthesized Silver Nanoparticles Using Mangifera indica Aqueous Leaf Extract against Multidrug-Resistant Pathogens - Yahya S. Alqahtani; Amal Bahafi; Kiran K. Mirajkar; Rakshith Rudrapura Basavaraju; Susweta Mitra; Shailaja S; Sunil S. More; Uday M. Muddapur; Aejaz Abdullatif Khan; P. Renuka Sudarshan; Ibrahim Ahmed Shaikh (MDPI AG, 2022)
An estimated 35% of the world's population depends on wheat as their primary crop. One fifth of the world's wheat is utilized as animal feed, while more than two thirds are used for human consumption. Each year, 17-18% of the world's wheat is consumed by China and India. In wheat, spot blotch caused by Bipolaris sorokiniana is one of the major diseases which affects the wheat crop growth and yield in warmer and humid regions of the world. The present work was conducted to evaluate the effect of green synthesized silver nanoparticles on the biochemical constituents of wheat crops infected with spot blotch disease. Silver nanoparticles (AgNPs) were synthesized using Mangifera indica leaf extract and their characterization was performed using UV-visible spectroscopy, SEM, XRD, and PSA. Characterization techniques confirm the presence of crystalline, spherical silver nanoparticles with an average size of 52 nm. The effect of green synthesized nanoparticles on antioxidative enzymes, e.g., Superoxide dismutase (SOD), Catalase (CAT), Glutathione Reductase (GR), Peroxidase (POX), and phytochemical precursor enzyme Phenylalanine Ammonia-Lyase (PAL), and on primary and secondary metabolites, e.g., reducing sugar and total phenol, in Bipolaris sorokiniana infected wheat crop were studied. Inoculation of fungal spores was conducted after 40 days of sowing. Subsequently, diseased plants were treated with silver nanoparticles at different concentrations. Elevation in all biochemical constituents was recorded under silver nanoparticle application. The treatment with a concentration of nanoparticles at 50 pp min diseased plants showed the highest resistance towards the pathogen. The efficacy of the green synthesized AgNPs as antibacterial agents was evaluated against multi drug resistant (MDR) bacteria comprising Gram-negative bacteria Escherichia coli (n = 6) and Klebsiella pneumoniae (n = 7) and Gram-positive bacteria Methicillin resistant Staphylococcus aureus (n = 2). The results show promising antibacterial activity with significant inhibition zones observed with the disc diffusion method, thus indicating green synthesized M. indica AgNPs as an active antibacterial agent against MDR pathogens.